Otimização da geração de energia em célula a combustível microbiana com Escherichia coli utilizando eletrodo modificado por eletrodeposição de polipirrol - Fung, Andrew Way Meng (2016)
The development of technologies to obtain renewable energy has received increasing attention nowadays. Microbial fuel cells (MFC) are chemical devices that uses microorganisms under anaerobic conditions to catalyze redox reactions in organic compounds for electricity generation. Recent research is focused to optimize the performance and efficiency of MFCs. One challenge is the need to test new conductive materials as electrodes in order to increase the electric potential in these devices. Polypyrrole is a conductive organic polymer which presents good electrical conductivity, high surface area, low cost and also biocompatibility. In this work, a double chamber MFC was built to generate electricity from glucose degradation by Escherichia coli. We assessed two types of electrodes: a graphite one, normally used in studies with MFCs, and graphite modified by electrodeposition of polypyrrole, obtained after synthesis. The potential difference was recorded using a data logger multimeter connected in series with the MFC and connected to a computer to obtain data in real time. For evaluation of biofilm formation on the surface of the electrodes scanning electron microscopy (SEM) was carried out. The MFCs had power density values ranging from 15 MW.m-2, in the experiment using graphite electrode 20 and MW.m-2 in the experiment using graphite electrode with polypyrrole. By the modification of the graphite surface with polypyrrole it was observed an increase in electrical activity and increased surface area of the electrode. In terms of cell efficiency, it was possible to observe an increased coulombic efficiency in the system containing polypyrrole (17.18%) compared with the system that lacked (7.31%), representing an improvement in flow of electrons from the substrate that can be converted into electricity. Therefore, it was shown in this work that the graphite electrode modified by electrodeposition of polypyrrole can be a viable and profitable alternative for use in MCC.